ENT 530 Social Media Portfolio: Themooi.co / Siti Nurhikmah Razlan - Razlan, Siti Nurhikmah (2020)
The mooi.co offering makeup stuff and the same time that can satisfy all which is makeup lover out there. We decided to sell cosmetic thing due to high potential demand among customers that favour all types of shades that we have. Relevance to our vision and mission, we want to offer makeup stuff without used too much chemical. As an example, jojoba oil is mainly used for small-scale applications such as pharmaceuticals and cosmetics. Besides, for our high demand lipstick we also use petroleum jelly which is Vaseline to relieve dry skin, including your lips. Our Born to Blush is specially formulated to give a pop of colour on cheeks whenever you need it. Their shades is highly pigmented, just a light stroke goes a long way. to the market. The mooi.co offering five types of makeup and haircare stuff which is Pillowlips, Lip Dessert, Born to Blush Blusher, Eyeshadow and Hair to Toe Mist. Our target market is universal. Despite the age, race or religion all groups of customers can purchase and use our products. Relevance with our tagline ‘You Can Wakeup Kiddos’, we want all customers satisfied with the outcomes. Lastly, I hope that this cosmetic online store will introduce such a good product and lifting local makeup brand in future.